A importância da observação da estrutura textual durante a catalogação de assunto de livros científicos em bibliotecas universitárias: uma análise realizada a partir da técnica de Protocolo Verbal - Reis, Daniela Majorie dos [UNESP] (2012)
Indexing is a form of description that looks to define concepts expressed in a document and to represent them according to a documental language. Some factors influence this process and can contribute to a more complete selection of terms that represent the document within an information system, which is previous knowledge about the subject of the document and the area where the professional is inserted. Another important factor to consider is the textual structure of documents that are indexed. Each document type has its own structure, but when the document in focus is the book, the textual structure analysis can be performed in order to facilitate the subject cataloging, because the professional who performs this procedure can get the terms in more appropriate spots. Thus, we seek to understand and investigate the indexer as a professional reader through the observation of their professional experiences acquired through the specific domain of university libraries, and the use of textual structure for the subject cataloging. To achieve this, an introspective technique for data collection, the Verbal Protocol, which is the manifestation of thoughts during the recording of any proceedings in this case, subject analysis, a procedure that leads to determination of issues will be applied. With the results obtained through literature research and data collection during subject cataloging, it was possible to observe which parts of the textual structure of scientific books are most frequently consulted by librarians at the analyzed universities and contributed to plan the “Modelo de ensino de leitura documentária para... (Complete abstract click electronic access below)